Flow characterization of microscale effusion and transpiration air cooling on single blade - Kim, Mingeon; Shin, Dong Hwan; Lee, Bong Jae; Lee, Jungho (Case Studies in Thermal Engineering, 2022)
Micro cooling has drawn attention as the next-generation cooling technique that is better than film cooling for a high-temperature turbine blade. Not to reduce the gas turbine efficiency while having high blade cooling effectiveness, it recommends that the cooling air does not invade or break the hot gas mainstream. This study deals with the flow and cooling phenomena by visualizing the flow around a single blade. The visualization was performed using a DPSS laser and a high-speed CCD camera imaging system. The smoke-wire visualization technique was employed to visualize the mainstream and oil atomized droplets to visualize the coolant flow. Single C3X blade with effusion cooling (hole diameter = 500 μm) and transpiration cooling (pore diameter = 40 μm) were selected as the target geometry. The visualization was carried out while varying the coolant flow rate. The visualized qualitative results showed that effusion cooling affects the mainstream at the blowing ratio of 8.0; however, transpiration cooling relatively stable the boundary layer up to the blowing ratio of 21.2. Additionally, the numerical simulation results were compared with the experimental data to analyze not only the flow characteristics but also the cooling characteristics.
Keywords: Air cooling; Blowing ratio; Cooling technique; Effusion cooling; Flow characterization; Flow visualisation; Micro cooling; Single blades; Transpiration cooling; Turbine blade; Effusion cooling; Flow visualization; Numerical simulation; Transpiration cooling; Turbine blade